المعلم والذكاء الانفعالي داخل الفصل الدراسي: مقارنة بين الفكر التربوي الإسلامي والدراسات التربوية المعاصرة - مامليسي، سامان علي محمد (كلية الإمارات للعلوم التربوية, 2018)
يهدف البحث إلى تسليط الضوء على أهمية الاعتماد على الذكاء الانفعالي في الإدارة الصفية من قبل المعلم، فالذكاء الانفعالي من الموضوعات النفسية المستجدة في الساحة التربوية والنفسية، إضافة إلى كونه معتمداً عليه في كثير من الشركات والمؤسسات لقياس أداء العاملين والموظفين وتقويمهم الختامي وبالتالي القرار على بقائهم في الوظيفة أو طردهم. لموضوع البحث التأثير الواضح على إدارة سليمة للفصل الدراسي واللجوء إليه كعقار تنشيط لإثارة الدافعية اللازمة والانتباه المطلوب تجاه النشاطات الصفية المتنوعة والفعاليات المتجددة. إذ المعلم يحتاج في إدارته للفصل إلى استخدام مهاراته والتحكم بانفعالاته والسيطرة على حنقه وغضبه إزاء الشغب وخلق المشاكل من الطلاب اللامبالين وخلخلة النظام الصفي. ويحاول البحث بيان أن الوقوع في متاهات التهديد واستخدام التعليقات اللاذعة واستخدام العنف لحل المشاكل المستحدثة والمتكررة الوقوع؛ يؤدي بالنهاية إلى إصابة المعلم نفسه- قبل المتعلمين- بالملل والشعور بالإحباط والحيرة وازدياد الضغط النفسي، وبالمقابل ينفر الطلاب من الموضوع المقرر ويزيد شعورهم بالسآمة واستيائهم من أساليب المعلم وتصرفاته القسرية، مما يقتل هممهم ويتدنى دافعيتهم. هذا وإن الفكر التربوي الإسلامي من خلال الإيحاءات القرآنية والإيماءات الكامنة في الأحاديث النبوية حث المربين على استخدام الرفق واللين والألفة مع الطلبة كي ينجذبوا إلى المعلومات المعروضة والمعارف المقدمة، وحذرهم من الوقوع في مآزق الحنق والغضب تجاه من يعلمونهم وطلب منهم إبعاد أنفسهم عن العنف والقسر أثناء التعليم. وإذا ما وصل المعلم إلى حالة من الهدوء الداخلي والاتزان العاطفي، فبالتأكيد إنه يسيطر على الحالات غير المرضية ويستطيع التفكير في حلها وقتئذ، دونما حاجة إلى خلق التوتر والتشويش وتكدير صفاء ذهن البقية من الطلاب.
The aim of this study is to highlight the significance of relying on emotional intelligence in classroom management by the teacher. Emotional intelligence is one of the psychological issues emerging in the educational and psychological fields, in addition to being relied on by many companies and institutions to measure the performance of workers and employees and their final evaluation about their remaining or dismissal. The subject of the study has a clear effect on the thorough management of the classroom and its use as an energizing drug to stimulate the necessary motivation and attention towards the various classroom activities and the renewed activities. The teacher needs in his administration of the period to use his skills and control his emotions and control of his anger and fury at the riots and created problems of the careless students and disruptive of the classroom system. The research attempts to show that falling into the maze of threats, using harsh comments and using violence to solve problems that have been created and repeatedly occurred; ultimately, the teacher himself - before the learners - becomes bored, frustrated, confused, and stressed. And their coercive actions kill them and diminish their motivation. The Islamic educational thought through the Quranic inspirations and gestures in the Prophet's Hadiths urged the educators to use kindness, tenderness and familiarity with the students in order to be drawn to the presented information and the provided knowledge, and to prevent them from falling into the pitfalls of anger and fury towards those who teach them and ask them to stay away from violence and coercion during education. If the teacher reaches a state of inner calm and emotional balance, he certainly controls the unsatisfactory situations and can think of solving them at the time, without a need for creating tension and confusion and smother the purity of the mind of the rest of the students.
Keywords: علم النفس التربوى -- الذكاء الانفعالي -- المعلمون التربويين -- الفكر الاسلامى -- الدراسات التربوية -- العصر الحديث